2022
DOI: 10.1177/03000605221118682
|View full text |Cite
|
Sign up to set email alerts
|

Spectral edge frequency during general anaesthesia: A narrative literature review

Abstract: Previous studies have attempted to determine the depth of anaesthesia with different anaesthetic agents using electroencephalogram (EEG) measurements with variable success. Measuring depth of anaesthesia is confounded by the complexity of the EEG and the fact that different agents create different pattens. A narrative review was undertaken to examine the available research evidence on the effect and reliability of spectral edge frequency (SEF) for assessing the depth of anaesthesia in adult patients under gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Although we found no broad changes in the EEG spectral power in our cohort, 8 of the 18 patients (44.4%) showed a significant reduction in the alpha power across sessions, a finding that was corroborated by the mixed-effect model in which a random effect for the subject was included. This change was accompanied by a reduction in the SEF95 to lower frequencies, indicating that, overall, there was a shift in the EEG signal to lower frequencies 26 . However, this result should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although we found no broad changes in the EEG spectral power in our cohort, 8 of the 18 patients (44.4%) showed a significant reduction in the alpha power across sessions, a finding that was corroborated by the mixed-effect model in which a random effect for the subject was included. This change was accompanied by a reduction in the SEF95 to lower frequencies, indicating that, overall, there was a shift in the EEG signal to lower frequencies 26 . However, this result should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 78%
“…This change was accompanied by a reduction in the SEF95 to lower frequencies, indicating that, overall, there was a shift in the EEG signal to lower frequencies. 26 However, this result should be interpreted with caution. No previous publication has reported a reduction in alpha power in infants, and only a single case of an adult patient exhibiting a reduction in frontal alpha power over 3 surgeries and across the course of 7 months has been published.…”
Section: Discussionmentioning
confidence: 83%
“…Practically, an SEF-95 of 10 to 12 Hz likely represents adequate anesthesia, indicating alpha oscillation presumably underscored by prominent delta and slow waves. 13 In contrast, a low SEF-95 between 2 and 6 Hz likely represents a delta-dominated EEG as during hypothermy and cardiopulmonary bypass. 14 During preanesthesia, we often observed a wide range of FO-RPAB values in the recording.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the original EEG, SEF simpli es the form of power variation of various waves in the range of 0-30 Hz. The smaller the value of SEF suggests that 95% of the total EEG power is concentrated in the low-frequency region and the depth of anesthesia deepens, and vice versa [15,16] . It has been shown that SEF is not in uenced by age and brain development, can more accurately and visually re ect EEG changes, correlates with the blood concentration of various anesthetic drugs, and can better re ect the intraoperative role of anesthetic drugs in maintaining the depth of anesthesia [17,18] .…”
Section: Discussionmentioning
confidence: 99%